The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/cncr.26549
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and risk factors for early‐stage adenoid cystic carcinoma of the major salivary glands

Abstract: BACKGROUND: Adenoid cystic carcinoma (ACC) is characterized by slow growth, frequent local recurrences, and distant metastasis (DM). However, these findings frequently are reported in patients with advancedstage tumors, but the outcomes of early-stage tumors are poorly defined. We sought to evaluate the risk factors for the development of DM in early-stage ACC. METHODS: We retrospectively reviewed the charts of 60 patients who were diagnosed with clinical early-stage (T1-2/N0) ACC to determine the risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 26 publications
(47 reference statements)
8
109
6
Order By: Relevance
“…Consistent with studies by Gomez et al [14,] and Agnes Oplatek [16] who demonstrated decreased survival in patients with cervical nodal metastasis, our data showed a decrease in survival, too. Whereas isolated lymph node involvement without distant metastasis may not have significantly altered survival in some studies, [17] lymph node involvement is a risk factor for subsequent distant metastasis [9]. The findings of the present study are concordant with those from other study [16] confirming the important impact of tumor site at diagnosis.ACC is wellknown for its indolent growth but common recurrence.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with studies by Gomez et al [14,] and Agnes Oplatek [16] who demonstrated decreased survival in patients with cervical nodal metastasis, our data showed a decrease in survival, too. Whereas isolated lymph node involvement without distant metastasis may not have significantly altered survival in some studies, [17] lymph node involvement is a risk factor for subsequent distant metastasis [9]. The findings of the present study are concordant with those from other study [16] confirming the important impact of tumor site at diagnosis.ACC is wellknown for its indolent growth but common recurrence.…”
Section: Discussionsupporting
confidence: 88%
“…The case series consisted of 19 that were scored as positive for MYB activation and comprised a roughly equal mixture of cribriform and predominantly solid histological forms of ACC (Supplemental Table 1). The latter are associated with increased risk of local-regional relapse, distant metastases, and poorer overall survival (4).…”
Section: Resultsmentioning
confidence: 99%
“…Although hormones or other sex-dependent biologic factors might explain a greater female:male ratio, whether the same factors affect disease behaviour or outcomes is unknown. Likewise, some-but not all-studies showed an association between advanced age and more advanced disease stage or dfs 9,25 . In the present study, advanced age (that is >60 years) did not affect dfs, implying that age alone does not modify the natural history of acc.…”
Section: Discussionmentioning
confidence: 97%
“…Surgery, the traditional mainstay of treatment for localized acc, results in improved survival [5][6][7][8] nodes 4,[9][10][11] . In cases in which surgery is not possible, radiotherapy alone has been used, but with inferior results 8,[12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%